HUBUNGAN ANTARA STRES KERJA DENGAN EFEKTIVITAS KOMUNIKASI INTERPERSONAL PASANGAN PADA KARYAWATI DI BANK MEGA KANTOR CABANG AREA JAKARTA SELATAN - FARISA NURDIANI; Ika Febrian Kristiana (Jurnal EMPATI, 2017)
Effectiveness of interpersonal communication on couple is message delivery process that are capable to achieve suitable understanding and comprehension between husband and wife, which content of information is delivered appropriately, and takes places in a pleasant situation. Work stress is physiological, psychological, and behavioral responses caused by job stressors. Effectiveness of interpersonal communication is influenced by work stress, where stress will make individual generate negative emotions such as disbelief and suspicion, showing hostility, and other negative interactions. This study aims to determine relationship between work stress and effectiveness of interpersonal communication on couple to woman employees at Bank Mega Branch Offices of South Jakarta Area. The subject of this research is woman employees of Bank Mega who is married. The sample of the study is 121 people. The sampling technique used is purposive sampling technique. The research data were collected using Work Stress Scale (35 valid aitems, α = .91) and Effectiveness of Interpersonal Communication on Couple Scale (30 valid aitems; α = .93) which have been tested on 45 woman employees of Bank Mega. Spearman correlation test results showed a negative relationship between work stress and effectiveness of interpersonal communication on couple which is indicated by correlation coefficient rxy = -.275 with p = .002 (p <.01). Negative relationship shows the higher work stress the lower effectiveness of interpersonal communication on couple, and the lower work stress the higher effectiveness of interpersonal communication on couple.